On the nature of CP Pup - Mason, E. (2013)
We present new X-ray and optical spectra of the old nova CP Pup (nova Pup 1942) obtained with Chandra and the Cerro Tololo Inter American Observatory (CTIO) 4 m telescope. The X-ray spectrum reveals a multitemperature optically thin plasma reaching a maximum temperature of 36^{+19}_{-16} keV absorbed by local complex neutral material. The time-resolved optical spectroscopy confirms the presence of the ?1.47 h period, with cycle-to-cycle amplitude changes, as well as of an additional long-term modulation which is suggestive either of a longer period or of non-Keplerian velocities in the emission line regions. These new observational facts add further support to CP Pup as a magnetic cataclysmic variable (mCV). We compare the mCV and the non-mCV scenarios and, while we cannot conclude whether CP Pup is a long-period system, all pieces of observational evidence point at an intermediate polar-type CV.